Autism and Phthalate Metabolite Glucuronidation - Stein, T. Peter (2013)
Exposure to environmental chemicals may precipitate autism spectrum disorders (ASD) in genetically susceptible children. Differences in the efficiency of the glucuronidation process may substantially modulate substrate concentrations and effects. To determine whether the efficiency of this pathway is compromised in children with ASD, we measured the efficiency of glucuronidation for a series of metabolites derived from the commonly used plasticizer, diethylhexyl phthalate. Spot urines were collected and analyzed for the fraction of each metabolite conjugated by isotope dilution-liquid chromatography mass spectrometry-mass spectrometry. The degree of glucuronidation was lower with the ASD group. The glucuronidation pathway may differ in some children with ASD.